Modulating hESC-derived cardiomyocyte and endothelial cell function with triple-helical peptides for heart tissue engineering. (February 2021) - Colzani, Maria; Malcor, Jean-Daniel; Hunter, Emma J.; Bayraktar, Semih; Polkinghorne, Murray; Krieg, Thomas; Cameron, Ruth; Best, Serena; Farndale, Richard W.; Sinha, Sanjay
Abstract: In this study, we investigated the role of cardiomyocyte (CM) and endothelial cell (EC) specific interactions with collagen in the assembly of an operational myocardium in vitro . Engineered cardiac patches represent valuable tools for myocardial repair following infarction and are generally constituted of a suitable biomaterial populated by CMs and supportive cell types. Among those, ECs are required for tissue vascularization and positively modulate CM function. To direct the function of human embryonic stem cell (hESC)-derived CM and EC seeded on biomaterials, we replicated cell-collagen interactions, which regulate cellular behaviour in the native myocardium, using triple-helical peptides (THPs) that are ligands for collagen-binding proteins. THPs enhanced proliferation and activity of CMs and ECs separately and in co-culture, drove CM maturation and enabled coordinated cellular contraction on collagen films. These results highlight the importance of collagen interactions on cellular response and establish THP-functionalized biomaterials as novel tools to produce engineered cardiac tissues. Graphical abstract: Image 1